Respostas

2014-07-07T17:20:56-03:00
 (a+1)² + 2 ( a+1) +1 =
(a+1)(a+1)+2(a+1)+1=0
a
²+a+a+1+2a+2+1=0
a²+4a+2=0                   a=1   b=4        c=2

Δ=b²-4ac
Δ=(4)²-4(1)(2)
Δ=16-12
Δ=4

     -b+-√Δ      -(4)+-√4       -4+-2            
x=--------------x=-------------x=-----------------
      2a              2.1              2                 

      -4+2           -2
x'=-------------x=--------x'=-1
         2              2
      -4-2        -6          
x"=--------x=---------x"=-3
      2            2    


x²-4x+4 + 3 ( x-2) (x+1)
x²-4x+4+3x-6+3x+3=0
x²+2x+1=0                             a=1         b=2      c=1

Δ=b²-4ac
Δ=(2)²-4(1)(1)
Δ=4-4
Δ=0

        -b+-√Δ         -(2)+-√0         -2+-0
x=-------------------x=----------------x=------------------
           2.a              2.1                  2
      -2+0          -2
x'=------------x'=-----------x'= -1
        2             2
      -2-0          -2          
x'=-----------x"=---------x"= -1
       2               2




2014-07-07T18:59:57-03:00
A)
(a+1)² + 2 ( a+1) +1 = [(a+1) + 1][(a+1) + 1] = (a + 2)(a + 2) = (a + 2)²
............
b)
x²-4x+4 + 3 (x-2) (x+1) = (x+2)(x-2) + 3(x-2)(x+1) = (x-2)[(x+2) + 3(x+1)] =
= (x-2)[x + 2 + 3x + 3] = (x-2)(4x+5)